The role of bacterial culture by bronchoscopy in patients with lung cancer: a prospective study - Koslow, Matthew; Shochet, Gali Epstein; Matveychuk, Alona; Israeli-Shani, Lilach; Guber, Alexander; Shitrit, David (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Background: Patients with lung cancer undergoing surgical and medical treatment are at increased risk for pulmonary complications. The importance of routine broncoscopy procedure in populations with lung cancer has rarely been defined. We aimed to determine the growth of potentially pathogenic microorganisms (PPM) among patients evaluated by bronchoscopy for lung cancer. Methods: This prospective study included 155 consecutive patients with lung mass or radiologic findings suspicious for malignancy. Baseline demographic, clinical and radiologic features were collected. Clinical features of infection were compared to microbiologic and histologic results. Results: The bacterial spectrum of lung cancer patients was similar to those without malignancy. The most frequently isolated organisms were Pseudomonas sp. and Staphylococcus aureus. Among all patients, bronchial bacterial positive PPM growth was noted in 30% (46/155). The significant PPM growth rate was three-fold higher among those with clinical signs of infection (P